The Well-Spoken SOA understanding the elements of an SOA in the context of management, security, governance, and the power of words. - Lipton, Paul
The American comedian and actor Steven Wright once said, "It doesn't make a difference what temperature a room is, it's always room temperature." Words are wonderful that way. They can give you a little blast of pleasure when used cleverly, but like everything else they are subject to fashion. For example, I was speaking at a technical conference recently when I overheard a person whom I know, who is well-respected in this field, say something along these lines : "You have to know how well your SOA is running. Knowing the overall health and responsiveness of your SOA is very important. You've got to get a handle on your governance." The goal was laudable, but the wording was off target.